PROGRESSIVE TRENDS IN INTERNATIONAL LAW FOR THE PREVENTION OF TRANSBOUNDARY ENVIRONMENTAL DAMAGE - Peruana de Derecho Internacional, Sociedad (2020)
Prevention and transboundary environmental damage. Both categories are the basis of along and unfinished international debate on the proposal of the Draft Articles for theDetermination of International Responsibility for the Injurious Consequences of Acts NotProhibited by International Law (international liability in case of loss caused by atransboundary harm resulting from hazardous activities), prepared in the InternationalLaw Commission in 2001. However, before and after the approval of the final text of theaforementioned project, States either regionally or globally have made efforts to codingfor the definition, prevention and punishment of this type of damage. The presentinvestigation has as purpose to carry out an examination of said international instrumentsthat from 1963 to 2018 have contributed substantially to the study of this type of damages,and to the delimitation of the formal and material guarantees established in favor of theStates; trying to crystallize also the gaps that normatively this matter faces. The actualityof the issue is even more evident when from our region, Latin America, processes havebeen developed before the International Court of Justice, on the affectation to the territoryand goods for transboundary environmental damages, v. Gr.: Argentina v. Uruguay,(2010), Ecuador v. Colombia, (2013), and the high procedural accumulation case (CostaRica v. Nicaragua and Nicaragua v. Costa Rica (2015).) It can not be ignored that Stateshave the obligation to guarantee that the activities carried out within their jurisdiction orits control does not cause harm to the environment of other States and exhaust all meansto avoid or prevent risks. The results to be obtained with the investigation are: determinewhat normative criteria have reached a standard of general application, and, establish theopportunities of regulations still pending for a better resolution of the processes submittedto competition from international jurisdictions.